Ketahanan UMKM dalam Pengembangan Ekonomi Lokal: Studi Ketergantungan Pasar pada Kawasan Kuliner Purwasera Purwokerto - Sabila Inayatul Kafiyah; Neisya Syafarina; Naerul Edwin Kiky Aprianto (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This study aims to analyze the resilience of Micro, Small, and Medium Enterprises (MSMEs) in local economic development, with a focus on market dependency in the Purwasera culinary area, Purwokerto. The study employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, documentation, and literature review, involving MSME actors and area management as informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that MSMEs play a strategic role in supporting local economic activities, as reflected in increased income and dynamic economic transactions. However, MSME resilience still faces challenges, particularly high dependency on student consumers, which leads to income fluctuations during academic holidays. In addition, low adoption of digital technology hinders market expansion and business competitiveness. This study concludes that strengthening MSME resilience requires market diversification, digital adoption, and capacity building to ensure sustainable local economic development..